Correlation between dental radiology knowledge and the ability to interpret panoramic radiographs among dental students: Study cross-sectional - Adawiyah, Rabiyatul; Agustin, Sylvia; Simbolon, Dame Rimmauli; Purnamasari, Cicih Bhakti; Martalina, Elliana; Arief, Erry Mochammad (Padjadjaran Journal of Dental Researchers and Students, 2026)
ABSTRACT Introduction: Knowledge is the result of human curiosity, and in dental education, students are required to understand the fundamentals of dental radiology. Panoramic radiography, as one of the most frequently used imaging modalities, plays an important role in supporting diagnosis; however, a limited understanding of basic dental radiology concepts often complicates the interpretation process. This study aimed to analyze the correlation between the level of dental radiology knowledge and the ability to interpret panoramic radiographs among preclinical dental students. Methods: This study employed a cross-sectional design using a questionnaire. A total sampling technique was applied, involving 146 students from the Faculty of Dentistry, Universitas Mulawarman. Bivariate analysis was conducted using Spearman’s rho correlation test. The variables assessed were dental radiology knowledge and panoramic radiograph interpretation ability. Results: The findings indicated that 49.3% of students had good dental radiology knowledge, 41.8% had good ability in interpreting panoramic radiographs, and 39.0% were good in both variables. Correlation analysis showed a statistically significant correlation between dental radiology knowledge and the interpretation of panoramic radiographs (Sig. [2-tailed] = 0.001). Conclusions: There is a significant correlation between dental radiology knowledge and the ability to interpret panoramic radiographs among dental students at Universitas Mulawarman.KEY WORDS: knowledge, dental radiology, interpretation, panoramic radiograph, studentsKorelasi pengetahuan dental radiologi dengan kemampuan interpretasi radiograf panoramik pada mahasiswa kedokteran gigi: Studi cross-sectionalABSTRAK Pendahuluan: Pengetahuan merupakan hasil dari rasa ingin tahu manusia dan dalam pendidikan kedokteran gigi mahasiswa diharuskan memahami dasar dental radiologi. Radiograf panoramik sebagai modalitas yang sering digunakan memiliki peran penting dalam menunjang diagnosis, namun keterbatasan pemahaman konsep dasar dental radiologi sering menyulitkan proses interpretasinya. Penelitian ini bertujuan untuk menganalisis korelasi antara tingkat pengetahuan dental radiologi dengan kemampuan interpretasi radiograf panoramik pada mahasiswa pra-klinik kedokteran gigi. Metode: Penelitian ini menggunakan desain cross-sectional dengan menggunakan kuesioner. Penelitian menggunakan teknik total sampling dengan jumlah 146 mahasiswa Fakultas Kedokteran Gigi Universitas Mulawarman. Analisis bivariat menggunakan uji korelasi spearman’rho. Variabel yang diamati adalah pengetahuan dental radiologi dan interpretasi radiograf panoramik. Hasil: Pengetahuan dental radiologi mahasiswa sebesar 49,3% baik, 41,8% baik dalam menginterpretasi radiograf panoramik, dan 39,0% baik pada keduanya. Uji korelasi antara tingkat pengetahuan dental radiologi dan interpretasi radiograf panoramik menghasilkan nilai Sig. (2-tailed) sebesar 0.001. Simpulan: Mayoritas mahasiswa memiliki pengetahuan dental radiologi dan interpretasi radiograf panoramik yang baik serta terdapat korelasi antara tingkat pengetahuan dental radiologi dengan interpretasi radiograf panoramik pada mahasiswa.KATA KUNCI: pengetahuan, dental radiologi, interpretasi, radiograf panoramik, mahasiswa